Association between cardiac dysfunction, arrhythmias and chronic liver diseases: A narrative review. (June 2020) - Arya, Sanjeev; Deshpande, Hemant; Belwal, Shantanu; Sharma, Preeti; Sadana, Punish; Chandrakant,; Rahman, Faizur; Gupta, Mayank; Uniyal, Bhupesh
Abstract: Background: In patients with liver diseases, the heart is among the most adversely affected organs. Most of the patients with well-compensated chronic liver disease do not seek hospital admission and they often stay at home. This group of patients is at high risk for cardiac-related morbidity and mortality which includes acute cardiac events and sudden cardiac death. Patients admitted in intensive care units with acute decompensation of chronic liver diseases, managing cardiac dysfunction, which is often associated with arrhythmias, pose a big challenge to the Intensivists and the Cardiologists. Objective: The primary objective of this review was to evaluate the association between cardiac dysfunction, arrhythmias and liver diseases. Other objectives were to evaluate the relationship of the corrected QT interval (QTc) with impending arrhythmias and mortality, and probable pathophysiology behind such occurrences. The finding would keep the Intensivists and Cardiologists prepared to deal with any eventuality. Data source: The clinical evidence was searched in the form of original peer-reviewed journal articles published until 2019. We used search engines which included Embase, Cochrane Library, Google Scholar and PubMed. Study selection: Clinical studies were selected for all objectives. However, preclinical studies were considered for pathophysiology. Data extraction: Titles and abstracts were screened first. Abstracts were read in full and then evaluated for eligibility. Data synthesis: From the searched studies, relevant studies meeting the objectives were analyzed and extracted. Duplicate and irrelevant articles were excluded from the review. Thereafter, full texts were reviewed for eligibility. Conclusion: It was found that a significant amount of interaction exists between the functioning of the liver and the heart. Approximately 50% of chronic liver disease patients develop cardiomyopathy, also known as cirrhotic cardiomyopathy (CCM), as it is found in patients with established liver cirrhosis. The main pathophysiology behind these actions is the bile acids that have the potential to cause cardiac hypertrophy. A prolonged QT interval, often seen in chronic liver diseases, is associated with an increased risk of cardiac morbidity and mortality due to the potential to cause arrhythmias. These morbidities and mortality can be prevented if electrocardiogram parameters especially QT/QTc values and echocardiographic findings depicting dysfunction are noted and acted upon. This cohort of patients needs to be brought under surveillance at the outpatient level or kept under close monitoring as an inpatient level of care, preferably is specialized or Intensive Care Units.